2020
DOI: 10.1007/s00449-020-02413-6
|View full text |Cite
|
Sign up to set email alerts
|

Statistical approach to evaluate effect of temperature and moisture content on the production of antioxidant naphtho-gamma-pyrones and hydroxycinnamic acids by Aspergillus tubingensis in solid-state fermentation

Abstract: Non-ochratoxigenic Aspergillus tubingensis G131 is a filamentous fungus that can produce naphtho-gamma-pyrones (NγPs), polyketide pigments that exhibit interesting antioxidant properties. This study aims to investigate the effect of two critical parameters, temperature and moisture content on the fungus grown in solid-state fermentation using agricultural by-products (vine shoots and wheat bran) as sole medium. From the kinetic productions of secondary metabolites NγPs (asperpyrone E, dianhydroaurasperone C, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Therefore, as biomass production was restricted, the fungus dedicated itself to producing a greater quantity of the metabolite LA. This behavior was also observed in [17], where the effect of humidity on the production of antioxidant naphtho-gammapyrones and hydroxycinnamic acids by Aspergillus tubingensis in SSF was studied. Here, biomass production decreased with increasing humidity, while metabolite production increased.…”
Section: Experimental Data Of Ssf Mathematical Modeling and Parametri...supporting
confidence: 60%
See 2 more Smart Citations
“…Therefore, as biomass production was restricted, the fungus dedicated itself to producing a greater quantity of the metabolite LA. This behavior was also observed in [17], where the effect of humidity on the production of antioxidant naphtho-gammapyrones and hydroxycinnamic acids by Aspergillus tubingensis in SSF was studied. Here, biomass production decreased with increasing humidity, while metabolite production increased.…”
Section: Experimental Data Of Ssf Mathematical Modeling and Parametri...supporting
confidence: 60%
“…It is important to note that most of the fungal SSF studies found so far have focused on the effect of varying the initial moisture content of the solid substrate while keeping the humidified air flow static throughout the bioprocess [15][16][17][18][19]. Furthermore, one study was proposed a humidity control strategies based in capillary-water supply to control temperature and RH in SSF tray bioreactor [14].…”
Section: Lactic Acid Maximization Using Dynamic Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the numerous characteristics of SSF is that they are developed in very narrow temperature ranges. The importance of temperature in the SSF process is that it could regulate the outcome of fermentation, such as enzyme inhibition increase or decrease of a particular metabolite (Carboué et al, 2020;Kumar et al, 2021). Furthermore, microorganisms have specific temperature ranges where they have optimal growth.…”
Section: Temperaturementioning
confidence: 99%
“…According to the previous reports on solid-state fermentation [18,29,30], temperature, bottling capacity, and water addition were selected as single factors to investigate their effects on the TMP production in wheat medium. With the method of control variables, the temperatures were 19 • C, 28 • C, 37 • C, 46 • C, and 55 • C (with fixed bottling capacity of 100 g/250 mL and water addition of 50 mL); the bottling capacities were 80 g/250 mL, 90 g/250 mL, 100 g/250 mL, 110 g/250 mL, and 120 g/250 mL (with fixed temperature of 37 • C and water addition of 50 mL); and the water additions were 30 mL, 40 mL, 50 mL, 60 mL, and 70 mL (with fixed temperature of 37 • C and bottling capacity of 100 g/250 mL).…”
Section: Single-factor Analysismentioning
confidence: 99%